HAKIKAT NILAI DASAR PENANAMAN PENDIDIKAN KARAKTER PADA PERADABAN AGAMA ISLAM - Muhammad yusron El-Yunusi; Muchammad Bachrul Alam; Nur ‘Aisyatir Rodliyah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
The theacing of Islamic education has a strategic position in the development of the quality of every human being in education as well as the character, attitude and practice of religious teachings. Therefore, Islamic religious value education is a very basic dimension for humans to change for the better in accordance with the guidelines of life. The religious element is based on Islamic religious values, which allows each individual or group examine and determine attitudes in the social evirontment, this also affect values in muslim civilization itself an adab or religious attitude that must exist in every person. The purpose of this study is to find out the nature of the basic values of instilling character education in Islamic religious civilization. This study uses a method with a literature study show that what are the various basic values of Islamic education and the essentialism of Islamic religious character education. So, overall that the basic value of education in Islamic civilization is that education must be done as well as possible so that education can be instilled in the character of very human being who is intellectual and has good manners.